Ketahanan Kubis Bunga Larisa F1 terhadap Serangan Plutella xylostela pada Aplikasi Beberapa Dosis NPK dan Tanaman Pagar - Putri, Sekar Utami; Kartina, Raida; Darma, Wika Anrya; Rahhutami, Ratih (Savana Cendana, 2024)
Cauli flower is a vegetable from the Brassicaceae family which has high economic value. However, flowering cabbage easily experiences a decline in economic value due to the production of flowering cabbage being attacked by Plutella xylostella. P.xylostella attacks can reach 50-100%, so integrated control is needed to be able to control it effectively and efficiently. Technical and biological cultural controls are the controls applied in this research. The aim of this research was to assess the resistance of flowering cabbage to P.xylostella attacks by applying hedge crops and NPK doses to flowering cabbage. The research was structured using a complete randomized block design with two factors. The first factor is the type of hedge plant, namely spring onions, rampai tomatoes and tagetes, while the second factor is the NPK dosage, namely 100, 200, 300, 400 and 500 kg/ha. The results showed that there was no real interaction between the variables of plant height, flower appearance time, flower weight and P.xylostella attack. However, the border tagetes type was able to suppress P.xylostella attacks. P. xylostella attacks reached 33%.